Nanostructured composites as active layer to boost cathode performance in Solid Oxide Fuel Cells - Caizán-Juanarena, Leire; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (My University, 2022)
Since the efficiency of Solid Oxide Fuel Cells (SOFCs) is largely limited by the high polarization resistance of the cathode, several strategies have been proposed to enhance the electrochemical activity of such electrodes. Among them, optimizing the electrode microstructure by using different preparation methods, such as infiltration and spray-pyrolysis deposition, have rendered excellent and durable electrochemical performance. In addition, the tailoring of the electrode/electrolyte interface by incorporating active layers have proven to be particularly useful to improve electrode properties. The present work proposes alternative active layers based on nanocomposites by combining the properties of the La0.8Sr0.2MnO3-d (LSM) cathode and different ionic conductors with fluorite-type structure. Different nanocomposite layers were prepared by spray-pyrolysis deposition at 450 ºC for 30 min on Zr0.8Y0.16O1.92 (YSZ) electrolyte, i.e. LSM-Ce0.9Gd0.1O1.95 (CGO) and LSM-Bi1.5Y0.5O3 (BYO). Thereafter, the LSM was screen-printed on the YSZ pellet and sintered at 1000 ºC. The nanocomposite active layers were studied by different structural and microstructural techniques, such as XRD, SEM-EDX and HRTEM. The electrochemical properties of active layers were also investigated by impedance spectroscopy at different dc-bias and distribution of relaxation times. Similarly, fuel cell tests were performed in a NiO-YSZ anode supported cell. The nanocomposite layers were dense with a thickness of approximately 700 nm. Specially LSM-CGO layers showed improved adherence to the electrolyte without the presence of cracks, delamination or undesired reaction. Cathodes with active layer showed Area Specific Resistance (ASR) associated with a lower charge transfer resistance and a fast oxide ion transport at the electrode/electrolyte interface.
Keywords: Nanoestructuras; Electrodos; Active layers; Nanocomposites; Interfaces; Solid oxide fue cells; Cathodes; Spray pyrolysis